Internalization of Social Tolerance Values Among Students at the Bahjatul Ulum Islamic Boarding School in Sukowono-Jember - Muhamad Umar Hasibullah (proceedings.icesy, 2026)
This study aims to analyze the process of transforming social tolerance values at the Bahjatul Ulum Islamic Boarding School in Sukowono, Jember. Using a descriptive qualitative approach, data was collected through in-depth interviews, observations, and document reviews as primary and secondary sources. The results show that the internalization of tolerance values occurs through the study of classical Islamic texts that emphasize moderation, the exemplary behavior of kyai and ustaz in being inclusive, and the practices of santri life in the dormitory that foster empathy and social skills. In addition, deliberative activities and cross-cultural interactions with the surrounding community reinforce the actualization of tolerance values in real life. These findings confirm that Islamic boarding schools play a strategic role as social laboratories that not only produce intellectually intelligent santri, but also those with moderate, inclusive characters who are ready to face the challenges of diversity in the modern era.